KEMAMPUAN BERBAHASA ANAK DENGAN SINDROM ASPERGER - Lilis Handayani Napitupulu (Jurnal Bahasa Indonesia Prima (BIP), 2023)
This study analyses the case of a child 6 years old with Asperger Syndrome with a particularly high specific cognitive, linguistic, and metalinguistic profile. The method of the study is using qualitative methods. The instrument used to measure the child’s ability is the Wechsler Intelligence Scale for Children (WISC). The test places a high value on answer justification, allowing the interviewer to capture different levels of metalinguistic awareness. Unlike those assessing sonority and sonography, the child provided poor language-linguistic responses on the sonority subtests. These different results are explained in terms of this child's specific difficulties with "open" language systems, such as semantics, despite his excellent "closed" language abilities. The discussion emphasizes the importance of assessing language skills at the aggregate level of gifted children with Asperger syndrome.